Correction: Quality of life in adults with Down syndrome: A mixed methods systematic review. - Ogochukwu Ann Ijezie; Jane Healy; Philip Davies; Emili Balaguer-Ballester; Vanessa Heaslip (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0280014.].